PANCASILA DALAM KONTEKS POSTMODERN - SYAHNAN HARAHAP (JURNAL MITRA MANAJEMEN, 2013)
ABSTRACTIn the postmodern context, Pancasila as a paradigm in the life of the nation is still relepanwith the changing times. Not outdated and obsolete with changing times. Pancasila as anumbrella ideology, way of life and the basic state, aspired as a driving force and can givedirection to the development and changes in the development process towards a better(conducive). Uniformity (uniformity) and unity (unity) is also a powerful weapon in the face ofall obstacles and challenges in the process of transforming information and technology for thebetterment of the state and nation. Thus we have to do deconstruction of the traditionalconcepts back to the tradition of the State and nation buildingKeywords: Pancasila, Ideology, way of life, the basic State